Motivasi Dan Komunikasi Relawan Museum Konferensi Asia Afrika - Hendra Hermawan; Suwandi Sumartias; Herlina Agustin (Jurnal Ilmiah Wahana Pendidikan, 2022)
Volunteers are generally defined as individuals who participate in a voluntary behavior they carry out an activity of free will without any coercion, receive no compensation and do profit over others. This research aims to analyze individual motivation as Volunteers/Friends of Asia Africa Museum during the Bandung Historical Study Games 2021. This research further elaborates the theory and concept of Self Determination Theory (SDT) to understand the position and possession of Autonomy, Competence, and Relatedness within the individuals. Through descriptive qualitative research methods, particularly by observation and in-depth interviews with volunteers, this research has found various motivations in each individual that are relevant to the concepts within Self-Determination Theory (SDT).